PENGARUH DISPLAY TOKO DAN MOTIVASI BELANJA BERDASARKAN KESENANGAN TERHADAP PEMBELIAN TIDAK TERENCANA PADA KONSUMEN THE OASIS FACTORY OUTLET BANDUNG - Rahma wahdiniwaty; Sri Septiani Bagja (JURISMA : Jurnal Riset Bisnis & Manajemen, 2013)
The phenomenon that occurs is the development of a retail business one of them shaped factory outlets, many strategies to attract consumers who do make an impulsive purchase, such as changing store displays, adding the facility more enjoyable for consumers. The unit of analysis in this study is consumers who make purchases at The Oasis Factory Outlet Bandung with a sample size of 100 respondents. The test statistic used is the calculation of Pearson correlation, regression analysis, correlation, coefficient of determination, hypothesis testing, and also use the help of an application program SPSS 17.0 for windows.The results showed that impulsive purchase at The Oasis Factory Outlet Bandung as a whole is included in both criteria, but the indicator display criteria show store poorly because of lack of attention to the preparation and tidiness of goods that is placed in front of the store. As for the hedonic shopping motivation variables included in either category. But for the indicators included in the category of gratification shopping quite well, this is due to inadequate facilities provided so that consumers are less comfortable when he was at The Oasis Factory Outlet Bandug. Influence of store displays and hedonic shopping motivations have a positive and significant impact on consumer impulsive purchase of The Oasis Factory Outlet Bandung. This means that the store displays and consumer motivations that can evoke hedonistic consumers to make unplanned purchases.